Zakonnicy w duszpasterstwie, diecezja augustowska czyli sejneńska - Jemielity, Witold (Prawo Kanoniczne, 1998)
After the establishment of the Diocese of Wigry in 1799, many priests returned to their mother dioceses (Wilno, Łuck, Żmudź) situated in the Tsardom of Russia. Bp M. Karpowicz and the Prussian Government received religious from convents which were being suppressed in the Tsardom in order to replace them. Many religious returned to their places of origin, which where part of the sector of Poland annexed by Prussia. This state of the matter was taken over by the Diocese of Augustów, that is of Sejny, which came into being in 1818, in place of the Diocese of Wigiy. The bishops of Wigry, and later - of Augustów, frequently received documents concerning the secularization of religious from Rome. After the establishment of the Seminary in 1826, the bishope reduced the number of petitions to the Apostolic See. Gradually the number of priests educated on the spot (in Sejny) increased. In the 1820’s Russia limited the departures of religious to the Kingdom and forced those, who went 70 ArŁm, II 144 к. 71; II 148 k. 54; II 149 k. 8. [ 2 3 ] ZAKONNICY W DUSZPASTERSTWIE 1 7 1 there illegally, to return. Anew wave of immigration took place after 1832, when most of the convents in the Tsardom were suppressed. The Diocese of Augustów, that is of Sejny, had only nine male religious convent and one female one. After the January Uprising four of them were suppressed, three supernumerary survived for a few years. Only the Capuchins in Łomża and the Marians in Mariampol remained until the beginning of the present century, while the Benedictine Sisters - during the whole period. The religious priests travelled to parishes during the period of Easter confessions, preached sermons during parish solemnities, substituted priests who were ill. They heard confessions in their churches also, especially during frequent solemnities attended by many faithful. In the buildings of the convents diocesan priests had their yearly retreats, some stayed there placed there for a period of penance by the bishop. The assistance of religious coming from Russia in the pastoral ministry appeared mainly at the start of the XIX century and, as a result of their secularization, for a longer period of time. The Diocese of Augustów, that is of Sejny, was enriched by religious spirituality. In the second half of the century there was a lack of this influence which (together with many governmental restrictions) gave pastoral ministry a more administrative character.